THE CONCEPT OF IDEAL IN CLASSICAL PHILOSOPHY - Клешня, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The articlefrom the standpoint ofculturaland philosophicalanalysisinunderstanding the phenomenon ofidealconceptsof the main representativesof classicalphilosophy.